A data model for processing financial market and news data. (19th October 2009) - Rabhi, Fethi A.; Guabtni, Adnene; Yao, Lawrence
Due to immense amounts of data being generated from financial markets in many different formats, professionals and academics face interoperability problems when analysing such data. This paper proposes a data model that gives a coherent view of the information available from financial market data repositories. The novel features of this data model include: modelling the behaviour of an electronic market as an extensible event-based class hierarchy, and using ontologies to represent financial data as a set of inter-related and meaningful events. Using this data model, we develop interoperable web services that process the data at a high level of abstraction using a Service-Oriented Architecture.